2012
DOI: 10.1016/j.jhazmat.2012.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fluoride adsorption using Al (III) modified calcium hydroxyapatite

Abstract: h i g h l i g h t sAl modified hydroxyapatite possessed a higher defluoridation capacity of 32.57 mg/g. Hydroxyl groups on the surface of Al-HAP was the adsorption sites for F − removal. Enhanced F − removal over Al-HAP was attributed to the modification with aluminum.a r t i c l e i n f o a b s t r a c tAluminum-modified hydroxyapatite (Al-HAP) was prepared and characterized using XRD and BET analyses. Al-HAP possessed higher defluoridation capacity (DC) of 32.57 mgF − /g than unmodified hydroxyapatite (HAP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(70 citation statements)
references
References 21 publications
2
68
0
Order By: Relevance
“…Effects of phosphate on fluoride removal were also reported by [146]. The tendency of the anions to form inner-sphere complexes was reported by [28,29,32,63,170,174,175,177,178,[180][181][182][183].…”
Section: Effects Of Anion Cation and Organicmentioning
confidence: 78%
See 1 more Smart Citation
“…Effects of phosphate on fluoride removal were also reported by [146]. The tendency of the anions to form inner-sphere complexes was reported by [28,29,32,63,170,174,175,177,178,[180][181][182][183].…”
Section: Effects Of Anion Cation and Organicmentioning
confidence: 78%
“…A similar observation was reported by [66] on defluoridation of drinking water using chitosan-based mesoporous alumina. Nie et al [146] reported maximum fluoride removal of 75% at pH of 5 and the adsorption decreased further as the pH increases on Al (III) modified calcium hydroxyapatite.…”
Section: Effects Of Ph On Fluoride Removalmentioning
confidence: 99%
“…Bioceramic hydroxyapatite has been used and modified in many ways for increasing the adsorption capability. Al-HAP had a surface area of 258.6 m 2 /g, which was almost 4 times larger than that of HAP (75.7 m 2 /g) (Nie et al 2012). …”
Section: Surface Area Of Adsorbentmentioning
confidence: 84%
“…Fluoride has been classified as a water pollutant by the World Health Organization (WHO). The presence of fluoride in drinking water, dependent upon concentration (5) and duration of continuous absorption (2), can be either helpful or harmful to humans. Maintaining a fluoride concentration of about 1 mg/L can prevent skeletal and dental problems, especially in children (2,6).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intake of excessive fluoride can cause serious concerns for public health (7). Fluorosis is one of the most important public health issues around the world (5). Dental and skeletal fluorosis is irreversible, and there is no treatment for it yet.…”
Section: Introductionmentioning
confidence: 99%